The Development of Innovative Pottery and Waybread Balm for Alleviate Muscle Pain by Professionals Engaged in Pottery Making - Varee, Acha; Songprakun, Wallapa; Jansiri, Utthawit (Journal of The Royal Thai Army Nurses, 2026)
This research this developmental and action research aimed to develop and evaluate the effectiveness of the “Mor Ong Long and Mong Ya En Yued” innovation (Earthenware Pot and TendonStretching Herb Bundle) in reducing muscle pain among pottery artisans. Methods The sample comprised pottery artisans from Muang Kung Village, divided into two groups: an Innovation Development Group (10 community leaders and artisans) for prototype creation and revision, and an Innovation Trial Group (30 individuals) randomly selected and divided into three subgroups. Key instruments included the Pain Scale record and satisfaction evaluation form. Data were analyzed using Kruskal-Wallis test statistics The results showed that The average satisfaction level with the massage across the three trial groups was not significantly different the mean satisfaction with the massage using the Oonglong pot and waybread balm for muscle stretching among the three sample groups did not differ significantly (X2 = 1.036, p = .596). However, the mean pain level after the massage using the Oonglong pot and Grass Balm for muscle stretching significantly differed between the groups (X2 = 16.009, p = .000). The third group, which received the massage with the Oonglong pot and waybread balm, experienced lower pain levels than the other groups. The Mor Ong Long and Mong Ya En Yued innovation is effective in reducing muscle pain and offers a viable alternative medicine approach that provides user satisfaction.